Ageing models and maintenance strategy for road tunnels. Issue 5 (3rd May 2020) - Han, Xingbo; Xia, Yongxu; Ye, Fei; Wang, Yongdong
Abstract: The ageing and deterioration of road tunnels due to environmental factors are inevitable. Rational and appropriate maintenance methods are required to maintain safety. This study aims to establish a maintenance strategy that determines the timing, location, and methods adopted to repair a degraded tunnel. Ageing models, which are key to maintenance strategy decision-making, are established with three failure modes—flexural capacity, convergence, and crack. Carbonation penetration from the inner surface of the lining, as well as chloride erosion from the outer surface of the lining, is considered in formulating the time-variant deterministic models for the three failure modes. Then, considering the uncertainties of the variables, statistical models of the structural response are obtained to calculate the probability characteristics. Also, the statistical model for the load effect is established based on the modified routine method. The probability of structural failure is determined based on the statistics of the structural response and the load effect models. Furthermore, a maintenance strategy is proposed at the system level with the performance-based maintenance method. Finally, an example is illustrated to demonstrate the application of the proposed method. The result shows that the standard deviation of the flexural capacity of the lining has similar time-variant characteristics as the means. The coefficient of vibration changes remains in a narrow interval during the ageing process. The tunnel lining crown and bottom have a higher probability of failure than other zones. Moreover, the failure probability of the positive moment zones is higher than that of the negative moment zones. The result can assist tunnel managers in developing a rehabilitation or replacement plan for the operation of tunnels.